Incidence of adverse outcomes related to untreated sexual partner in congenital syphilis in the state of Paraná (Research, Society and Development, 2023)
Syphilis is a predominantly sexually transmitted disease caused by the bacterium Treponema pallidum, which can spread through the bloodstream, facilitating what we call vertical transmission or transplacental infection in pregnant women who are infected. The transmission of the bacterium from a pregnant woman to her baby can occur at any stage of pregnancy and at any stage of the disease, even allowing for direct transmission during childbirth - through contact of the newborn with the mother's vaginal lesions if she has them. For the purpose of compulsory notification, it is classified by the Ministry of Health (MS) as acquired syphilis, congenital syphilis (CS), and gestational syphilis, with CS being of greater concern due to the high number of cases that lead to serious outcomes for both pregnancy and the child. However, early screening for acquired and/or gestational syphilis is necessary to prevent these undesirable outcomes. Additionally, it is important to ensure that sexual partners receive proper diagnosis and treatment, as horizontal transmission (between sexual partners) is a significant cause of reinfection in previously adequately treated pregnant women. The aim was to measure the incidence of negative outcomes related to the lack of treatment of sexual partners in cases of congenital syphilis in the state of Paraná. In conclusion, it was found that the non-treatment of the sexual partner carries a higher risk to the life of newborns diagnosed with congenital syphilis.